Lights, camera and action in the implementation of central venous catheter dressing - Maria Verônica Ferrareze Ferreira; Simone de Godoy; Fernanda dos Santos Nogueira de Góes; Fernanda de Paula Rossini; Denise de Andrade (Universidade de São Paulo, 2015)
Objective: to develop and validate an educational digital video on changing the dressing of short-term, non-cuffed, non-tunneled central venous catheters in hospitalized adult patients. Method: this is a descriptive, methodological study based on Paulo Freire's assumptions. The development of the script and video storyboard were based on scientific evidence, on the researchers' experience, and that of nurse experts, as well as on a virtual learning environment. Results: the items related to the script were approved by 97.2% of the nurses and the video was approved by 96.1%. Conclusion: the educational instrument was considered to be appropriate and we believe it will contribute to professional training in the nursing field, the updating of human resources, focusing on the educational process, including distance education. We believe it will consequently improve the quality of care provided to patients with central venous catheters.